Perfil de expressão gênica e níveis de citocinas em macrófagos caninos com diferentes graus de sucetibilidade à infecção por Leishmania infantum - Andréia Pereira Turchetti (2014)
Visceral leishmaniasis is an important zoonosis caused by Leishmania infantum infection, which is transmitted by sand flies and has the domestic dogs as its main definitive host. Although there are several studies about the immune response of humans and laboratoryanimals to leishmaniasis, very little is known about the immune response of dogs to the disease. Dogs can either develop clinical signs and eventually died or remain as asymptomatic carriers. The reasons for this difference in susceptibility are still unknown. In order to investigatewhether the innate immune system is associated with this difference, we profiled the basal expression of important genes in innate immunity (Nramp1, NOD1, NOD2, TLR1, TLR2, TLR3, TLR4, TLR5, TLR6, TLR7 and TLR9) in canine monocyte-derived macrophages from animals negative to leishmaniasis, and cytokines (IL-10, IL-12, TNF- and IFN-) and nitric oxide in the culture supernatant of macrophages resistant or susceptible to in vitro infection by L. infantum. Constitutive expression of TLR9 and NOD2 are negligible, NOD1, LR1 and TLR7 are low and Nramp1 and TLR2 to 6 are higher in canine monocyte-derived macrophages. There was no significant difference in expression of different genes between animals resistant or susceptible to canine visceral leishmaniasis. The secretion of TNF- was higher in resistantanimals 24 hours after infection when compared to susceptible animals, as well as the secretion of IFN- at 72 hours post infection. The secretion of IL-10 was lower in resistant animals 24 hours after infection. There was no difference in secretion of IL-12 between resistant and susceptible dogs. There was no detectable production of nitric oxide in resistant or susceptible animals. Pearsons correlation study identified only a negative correlation between NOD2 gene expression and intracellular survival of L. infantum in animals resistant to visceral leishmaniasis. This study contributed to better understand the innate immune system of dogs, specially its response to the infection by L. infantum